Nursing Care for Community Health Deficit in The Aggregate of Tuberculosis Patients with Health Behavior Promotion Interventions - Firjatullah, Cassia Daras; Ati, Niken Asih Laras (Al-Hijrah Indonesia, 2024)
Efforts to control Tuberculosis (TB) are carried out in various ways, including activities to increase public knowledge about TB. Health Behavior Promotion Efforts are expected to increase changes in patient or client behavior so that they have the will and ability that are conducive to improving overall health. The aim of this research is a case study of community nursing care by providing intervention and implementation in selected target villages. The intervention provided is Promotion of Health Effort Behavior. The sample size was 87 respondents from selected area using the Cluster Sampling technique. Data collection instruments for taking cases managed in this scientific work use clean and healthy living behavior instruments, knowledge instruments about healthy homes, Knowledge Instruments on the Role of the Family as PMO (Drug Dispensing Supervisor), TB Screening and Scoring Instruments, procedures of Hand Washing. The intervention was carried out with Simple Inhalation Therapy Using Eucalyptus Oil Steam accompanied by a physical examination and vital signs measurements. The results of the research show that there is an effect of education on public knowledge with a p value (p= 0.000), the results of implementing the hand washing demonstration show results (p = 0.000) which means there is an effect of hand washing demonstration on public knowledge, while from the implementation of simple inhalation therapy with eucalyptus oil vapor the results were (p = 0.017) which means there is an effect of simple inhalation therapy with eucalyptus oil vapor on the patient's RR and SPO2. From the existing results, effective nursing implementation is carried out for TB prevention is the identification of health behavior efforts that can be improved, screening and health education, as well as the implementation of simple inhalation of eucalyptus oil vapor in TB patients.